Implementasi Pembuatan Akta Postnuptial Agreement oleh Notaris Pasca Putusan Makamah Konstitusi Nomor 69/PUU-XIII/2015 (Studi di Wilayah Kota Denpasar) - Ryan Permana Wijaya; I Nyoman Sujana; Putu Ayu Sriasih Wesna (Fakultas Hukum, Universitas Warmadewa, 2022)
This study aims to determine and analyze the existence and implementation of postnuptial agreement deeds after the Constitutional Court Decision Number 69 / PUU-XIII / 2015 (hereinafter referred to as the MK 69/2015) in Denpasar City. In essence, the Constitutional Court Decision 69/2015 provides an opportunity that a marriage agreement can be made during the marriage (postnuptial agreement). In order to ensure that the value of justice can actually be realized, it is necessary to study the implementation of the postnuptial agreement deed drafting. Based on this, two problems can be formulated as follows: (1) how is the existence of the postnuptial agreement deed after the Constitutional Court Decision 69/2015 in Denpasar City ?; (2) how is the implementation of the postnuptial agreement deed after the Constitutional Court Decision 69/2015 in Denpasar City? This research is an empirical legal research with descriptive-qualitative characteristics. The results showed that the making of the postnuptial agreement deed by a notary after the MK 69/2015 decision in the Denpasar City area proved to exist and was first made in 2017. The implementation of the postnuptial agreement deed by a notary after the MK 69/2015 decision in the Denpasar City area has not yet been implemented effective, for 2 reasons, namely differences in views on the calculation of the time frame for the application of postnuptial agreement deeds in the internal notary profession and a lack of understanding of the urgency of marriage agreements among people in the city of Denpasar.